2017
DOI: 10.1111/febs.14193
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the interactome of HPV E6 and E7 oncoproteins with the ubiquitin‐proteasome system

Abstract: Protein ubiquitination and its reverse reaction, deubiquitination, regulate protein stability, protein binding activity, and their subcellular localization. These reactions are catalyzed by the enzymes E1, E2, and E3 ubiquitin (Ub) ligases and deubiquitinases (DUBs). The Ub-proteasome system (UPS) is targeted by viruses for the sake of their replication and to escape host immune response. To identify novel partners of human papillomavirus 16 (HPV16) E6 and E7 proteins, we assembled and screened a library of 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 60 publications
(92 reference statements)
1
80
0
Order By: Relevance
“…This result suggests that E7 may increase DLG1 protein levels probably by contributing to its stabilization and/or preventing its degradation. In line with this, it was recently reported that HPV E7 interacts with different components of the ubiquitinproteasome system including proteins that reverse the ubiquitination process, and, in this way, E7 might interfere with the degradation of certain cellular substrates [42]. It is also possible that E7 induced signal pathways that drive changes in DLG1 posttranslational modifications, rendering it more resistant to proteasomal degradation.…”
Section: Discussionmentioning
confidence: 80%
“…This result suggests that E7 may increase DLG1 protein levels probably by contributing to its stabilization and/or preventing its degradation. In line with this, it was recently reported that HPV E7 interacts with different components of the ubiquitinproteasome system including proteins that reverse the ubiquitination process, and, in this way, E7 might interfere with the degradation of certain cellular substrates [42]. It is also possible that E7 induced signal pathways that drive changes in DLG1 posttranslational modifications, rendering it more resistant to proteasomal degradation.…”
Section: Discussionmentioning
confidence: 80%
“…These studies assembled and screened a library of 590 cDNAs related to the UPS that covered about 50% of the human ubiquitination system, together with co-immunoprecipitation to confirm novel cell target protein-E6 interaction. Results indicated various new target proteins, including three RING-type Ub ligases MGRN1, LNX3 and LNX4 [38,103]. MGRN1 was shown to interact with E6 proteins from LR HPV-6 and HR HPV types 16, 18 and 33, as well as β-types HPV types 8 and 38.…”
Section: E6 Oncoprotein and Ubiquitin Ligasesmentioning
confidence: 99%
“…Ubiquitin is transferred to target proteins by the ubiquitination cascade: first, ubiquitin is activated and bound by an E1 ubiquitin-activating enzyme, then transferred to an E2 ubiquitin-conjugating enzyme and, finally, transferred to lysine residues on the target protein by E3 ubiquitin-protein ligase [36,37]. So far, studies have identified two E1 activating enzymes, 40 E2 conjugating enzymes, around 800 E3 ubiquitin-protein ligases and about 100 DUBs [38]. While all components of the UPS are of great importance for ubiquitination, individual ubiquitin-protein ligases may be valuable viral targets as they are involved in substrate recognition, and hence define the specificity of the system.…”
Section: The Ubiquitin Proteasome Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of The FEBS Journal, Poirson et al . have made a global examination of the interactions of the two major human papillomavirus (HPV) oncoproteins, E6 and E7, with components of the UPS. Over 200 different HPV types exist, but the major interest in this group of viruses stems from the fact that a small number of HPV types are major causes of human cancer, with cervical cancer being the most frequent .…”
mentioning
confidence: 99%